Highly skilled migrant and non-migrant women and men: How do differences in quality of employment arise? - Yvonne Ria\~no (Administrative Sciences, 2021)
Research shows that highly skilled migrant women often have poor quality jobs or no employment. This paper addresses two research gaps. First, it provides a comparative perspective that examines differences and commonalities in the quality of employment of four highly skilled groups: migrant- and non-migrant women and men. Four statistical indicators are examined to grasp these differences: employment rates, income, adequacy of paid work, and employment status. The results highlight the role of gender and country of birth: Swiss-born men experience the best employment quality, and foreign-born women the worst. Second, it offers a family perspective to study how the employment trajectories of skilled migrant women develop in time and place in relation to their partners'. The qualitative life-course analysis indicates that skill advancement is more favourable for migrant and non-migrant men than for migrant and non-migrant women. However, skill advancement for migrant women depends greatly on the strategies enacted by domestic partners about how to divide paid employment and family work, and where to live. The statistical study draws on recent data from Swiss labour market surveys. The life-course analysis focuses on 77 biographical interviews with tertiary-educated individuals. Participatory Minga workshops are used to validate the study results.
Keywords: 350; migration; highly skilled; labour market outcomes; quality of employment; employment trajectories; employment inequalities; family; gender inequality; life-course analysis; participatory research; mixed methods